SWIMMING AS A LEISURE PHYSICAL ACTIVITY DURING THE 2020-2021 PANDEMIC COVID-19 IN CLUJ-NAPOCA - Iulia JULEAN; Remus VĂIDĂHĂZAN (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2021)
The Covid-19 pandemic has had a negative impact on the global community, leading to restrictive measures in all areas of activity, including sports. Starting with March 2020, most physical activities have ceased, due to the establishment of the state of emergency in Romania. Swimmers were restricted from accessing their main training facilities and were no longer allowed access to the pools. After a more sedentary period, in which each of us tried to adapt to the existing situation, the need to be involved in sports, the need for movement, and the need for socialization was growing. Thus, the instructors tried to find out alternatives to continue athletes training, so they do not completely lose their physical fitness. Some managed to continue their training in the water, at other pools, others organized workouts outside the pool, maintaining their physical condition at an optimal level. In fewer cases, coaches continued training with athletes online. The purpose of this study was to discover the training strategies applied by swimming coaches during the pandemic, during the State of emergency and the Alert state, in Cluj-Napoca. The results of our study can be used, in the future, by students, teachers and instructors to better reorganize their physical activities, especially swimming, when a special situation arises again.